Structural design and characterization of hybrid hierarchical lattice structures based on sheet-network Triply periodic Minimal surface topology - Giuseppe Di Frisco; Ramin Yousefi Nooraie; Mario Guagliano; Sara Bagherifard (Materials & Design)
The ability to adjust topological features of lattice structures offers a great potential to finely calibrate their physical and mechanical response to precisely meet specific requirements. This study explores a new topological design that leverages the internal porosity of Triply Periodic Minimal Surfaces (TPMS) unit cells to optimize and control their mechanical properties. A smaller-scale TPMS lattice structure was integrated within the internal volume of the sheet-network Schwarz Primitive TPMS cell, culminating in a hybrid hierarchical architecture. Various TPMS topologies with distinct mechanical behavior and varying relative density combinations were examined. Experimental and numerical approaches were developed to reveal the structure’s deformation behaviour and quantify stiffness, anisotropy, quasi-static uniaxial compressive strength, and energy absorption capacity. The topological design of the internal lattice was found to play a key role in defining the mechanical performance of the integrated structures, leading to enhanced energy absorption up to 4 times that of the reference structure. Moreover, all the studied hierarchical topologies exhibited a lower Emax/Emin ratio in comparison to the reference topology, indicating more isotropic performance of the hybrid designs (upto 40% reduction of anisotropy). The findings underscore the significant promise of hybrid hierarchical design methodologies in attaining lattice structures with tailored properties.